Case studies in psychotherapy - Wedding, Danny; Corsini, Raymond J. (Cencage Learning, 2014)
Using compelling contemporary and classic cases, CASE STUDIES IN PSYCHOTHERAPY brings to life essential concepts and practices in psychotherapy. The Seventh Edition of this popular casebook features intriguing new cases added to illustrate Psychoanalysis, Client-Centered Therapy, Existential Therapy, Interpersonal Therapy, Contemplative Therapies, and Therapy in a Multicultural context. There's also an entirely new chapter on Positive Psychotherapy. The book maintains its parallel structure with the Tenth Edition of Wedding and Corsini's CURRENT PSYCHOTHERAPIES, providing you with the most comprehensive look at psychotherapy available today. All of these insightful cases are chosen for intrinsic interest, clarity of presentation, and the ability to most effectively demonstrate the basic techniques and methods of the theory being illustrated